A Comparison of the Effectiveness of Two Computer-Based Learning Aids - Howe, Piers D. L.; Lodge, Jason M.; McKague, Meredith (Frontiers in Education, 2018)
Instructors are increasingly using computer-based educational technologies to augment their courses. As answering quizzes has been shown to be one of the most effective learning strategies, a growing number of computer-based learning aids use quizzing. So which of these learning aids should instructors recommend to their students? These learning aids typically either present the student with a number of potential answers and require that they recognise the correct answer (i.e. a multiple-choice quiz) or else they might the student to recall the answer without assistance (i.e. a free recall quiz). Numerous lab-based studies have shown that recall-based quizzes promote more learning and result in higher performance in a subsequent exam/test than recognition-based quizzes. In the present study, we investigated to what extent this finding holds in an actual university setting with two commercially-available learning aids. We found that while both types of learning aid proved to be effective, we could find no evidence that the recall-based learning aid was more effective than the recognition-based learning aid. In light of this, we discuss possible reasons why the laboratory findings did not readily translate into an actual university setting and make practical recommendations for what sort of computer-based learning aid instructors could incorporate into their university courses.